In-Coating Phenyl Phosphonic Acid as an Etch-Primer Corrosion Inhibitor System for Hot Dip Galvanized Steel. Issue 9 (11th June 2015) - Glover, C. F.; Subramanian, R.; Williams, G.
Abstract : In-coating phenyl phosphonic acid (H2 PP) additions are investigated as inhibitors of corrosion-driven organic coating disbondment on hot-dip galvanized (HDG) steel surfaces. In-situ scanning Kelvin probe (SKP) experiments under atmospheric corrosion conditions are used to study the influence of the quantity of dissolved H2 PP in the organic coating on the kinetics of delamination. It is demonstrated that increasing levels of in-coating H2 PP progressively lengthen the time for organic coating delamination to become established. Once underfilm corrosion becomes initiated, rates of cathodic disbondment are significantly slowed by H2 PP additions in comparison with the uninhibited case. From the observed delamination kinetics, an inhibition mechanism is proposed whereby H2 PP additions interact with the underlying zinc to form an interfacial salt layer which blocks underfilm oxygen reduction. The contribution of other possible modes of inhibition, such as H2 PP release from the coating into the external defect electrolyte and a buffering of underfilm pH, are also discussed.